Eksistensi Pendidikan Islam di Lingkungan Minoritas Muslim: Studi Kasus di Lembang Sereale, Toraja Utara: The Existence of Islamic Education in Muslim Minority Environments: A Case Study in Lembang Sereale, North Toraja - Salmiati Salmiati; Lismawati Lismawati; Nurlina Jalil; Nurpayani Nurpayani (Al-Musannif, 2023)
This research is motivated by the fact that it is not uncommon for divisions between minority and majority groups to occur due to religious differences. The purpose of this research is to reveal the reality, challenges, and solutions in the implementation of Islamic education in the Muslim minority environment. This research uses case studies that intend to understand the problem in depth so that cases can be examined using complete data or information. As a result of the research, it was found that the implementation of Islamic education in Lembang Sereale, North Toraja Regency takes place harmoniously because all community members understand and apply the values of tolerance. The challenges faced are the absence of worship facilities, access to residents’ houses, which are far apart, making it difficult for religious extension workers to carry out their duties, the absence of Islamic Religious Education subject teachers, and the lack of guidance and motivation from parents due to limited knowledge and busyness. A solution step is support from the government of Lembang Sereale in response to the need to support the implementation of Islamic education. In addition, it takes the active role of religious instructors to provide religious knowledge.